Introduction and Decolonial Pedagogies, Multilingualism and Literacies - Bock, Zannie; Stroud, Christopher; Menezes de Souza, Lynn Mario T. (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The Introduction gives an overview of the journal contents and a short account of the genesis and structure of the module within which the papers, poems, and artefacts were produced.